Iva xanthiifolia leaf extract reduced the diversity of indigenous plant rhizosphere bacteria - Jia-wen Wu; Feng-lan Li; Shu-kuan Yao; Zi-yi Zhao; Xu Feng; Rong-ze Chen; Yong-qing Xu (BMC Plant Biology, 2023)
Abstract Background Iva xanthiifolia, native to North America, is now widely distributed in northeastern China and has become a vicious invasive plant. This article aims to probe the role of leaf extract in the invasion of I. xanthiifolia. Methods We collected the rhizosphere soil of Amaranthus tricolor and Setaria viridis in the invasive zone, the noninvasive zone and the noninvasive zone treated with extract from I. xanthiifolia leaf, and obtained I. xanthiifolia rhizosphere soil in the invasive zone. All wild plants were identified by Xu Yongqing. I. xanthiifolia (collection number: RQSB04100), A. tricolor (collection number: 831,030) and S. viridis (collection number: CF-0002-034) are all included in Chinese Virtual Herbarium ( https://www.cvh.ac.cn/index.php ). The soil bacterial diversity was analyzed based on the Illumina HiSeq sequencing platform. Subsequently, taxonomic analysis and Faprotax functional prediction were performed. Results The results showed that the leaf extract significantly reduced the diversity of indigenous plant rhizosphere bacteria. A. tricolor and S. viridis rhizobacterial phylum and genus abundances were significantly reduced under the influence of I. xanthiifolia or its leaf extract. The results of functional prediction showed that bacterial abundance changes induced by leaf extracts could potentially hinder nutrient cycling in native plants and increased bacterial abundance in the A. tricolor rhizosphere related to aromatic compound degradation. In addition, the greatest number of sensitive Operational Taxonomic Units (OTUs) appeared in the rhizosphere when S. viridis was in response to the invasion of I. xanthiifolia. It can be seen that A. tricolor and S. viridis have different mechanisms in response to the invasion of I. xanthiifolia. Conclusion I. xanthiifolia leaves material has potential role in invasion by altering indigenous plant rhizosphere bacteria.